A primer on the pricing of electric energy options in Brazil via mean-reverting stochastic processes - Abdinardo Moreira Barreto de Oliveira; Anandadeep Mandal; Gabriel J. Power (Energy Reports, 2019)
Pricing option contracts on electricity remains methodologically challenging, with a lack of clearly defined and robust methods. In particular, little is known about pricing options in Brazilian energy markets, despite their economic significance. Using weekly price data (R/MWh) on four electrical subsystems from the Chamber for Commercialization of Electrical Energy, we estimate models to price Brazilian electricity energy options. This paper has three objectives: (i) to identify the occurrence of change-points (regime-switching) in time series of Brazilian energy spot prices; (ii) to determine the best Stochastic Differential Equation (SDE) with which to model Brazilian energy spot prices and (iii) to price five types of options used to manage electricity price risk in Brazil. We show that the change-point occurred between 2002 and 2018. During this period, the long-run marginal cost of production was the most affected. Furthermore, we find that the Ornstein-Uhlenbeck/Vasicek stochastic process and resulting SDE best explains electricity prices in Brazil, even with the occurrence of structural changes. Finally, our results indicate that Asian-style options are the least costly option contracts to manage electricity price risk in Brazil.
Keywords: 330; Energy options; Monte Carlo simulation; Stochastic processes; YUIMA